Sexual Violence Against Minors: A Case Report - Meidiana Sagita; Budi Suhendar; Farah P. Kaurow (Publikasi Indonesia, 2025)
Introduction: Sexual violence against children in Indonesia has significantly increased, with 50.78% of children aged 13–17 years having experienced violence in their lifetime and 33.64% within the past 12 months (SNPHAR, 2024). This case highlights the crucial role of medical professionals in victim identification and protection. Methods: This study is a clinical descriptive case report of a 10-year-old girl who was sexually assaulted by a 60-year-old man in Serang Regency. Examinations included anamnesis, physical and genital assessment, visum et repertum, and coordination with the Women and Children Service Unit (PPA). Results: The victim presented with genital pain and white discharge. Examination revealed a thick annular hymen with abrasions at 4–9 o’clock direction, indicating a fresh lesion ±1 day after the assault. No anal injury was found. The victim complained of dysuria. The perpetrator previously gave the child Rp2,000–Rp10,000 as part of a grooming pattern. The victim’s general condition was stable (compos mentis, normal blood pressure, good nutritional status). Conclusion: This case emphasizes the importance of early detection, aseptic wound care, analgesic administration, hepatitis B and tetanus immunization, and psychological support. A trauma-informed and empathetic approach is essential for recovery and accurate forensic documentation to ensure justice for child sexual assault victims.